Experimental study on anti angiogenesis of recombinant mouse angiostatin gene in mice with gallbladder carcinoma - Wang, Chunlin; Jiang, Tao; Zhu, Yunxie (Cellular and Molecular Biology, 2022)
Gallbladder cancer is one of the gastrointestinal tumors with an extremely poor prognosis. Its incidence rate is gradually increasing worldwide, and the rate of radical resection surgery is extremely low. Not sensitive to radiotherapy and chemotherapy, with a very poor prognosis. This study aimed to investigate whether the recombinant mouse angiostatin gene transfected anti-angiogenic gallbladder cancer cells can express angiostatin protein with the activity of inhibiting the growth of vascular endothelial cells and the inhibitory effect on the growth of gallbladder cancer. The recombinant mouse angiostatin gene eukaryotic expression plasmid was transfected into the gallbladder cancer cell line by applying liposome LIPOFECTAMINE 2000, and its activity was detected by vascular endothelial cell proliferation analysis. The results show that angiostatin can inhibit the growth of transplanted gallbladder cancer, and as the number of injections increases, the inhibition rate of gallbladder cancer growth also increases. At the end of the experiment, the total inhibition rate of gallbladder cancer growth reached 95% 5%, 20%, 30%, 40% gradually increase. Therefore, angiostatin has potential clinical application value in gene therapy of gallbladder cancer.